Diversity of floral insect visitors of mango during blooming period at Pantnagar - USHA, USHA; SRIVASTAVA, POONAM; GOSWAMI, VIMLA (The Indian Journal of Agricultural Sciences, 2014)
A total of 20 insect species were observed visiting on mango flowers belonging to eight species of the order Diptera, seven species of Hymenoptera, three species of Lepidoptera, one species of Hemiptera and one species of Coleoptera. The Dipterans constituted major group of insects visiting on mango flowers. Among the dipterans, syrphids (Family: Syrphidae; subfamilies: Syrphinae and Eristalinae) were observed the most frequent visitors, constituted (44.67%) the major group of visitors. The syrphids species included Episyrphus balteatus DeGeer, Melanostoma orientale Weid, Syrphus corollae Fab. and Eristalis tenax L. Of these, E. balteatus exhibited marked higher incidence on mango and as compared to other syrphids. Besides syrphids, other dipterans, viz. Musca domestica belonging to the family Muscidae and subfamily Muscinae, were also observed as the occasional visitors (0.50 per cent) on mango flowers. The Hymenopterans were monitored as second major group of insects found visiting on mango flowers. Of these, the family Apidae and subfamily Apinae contributed 40.95% and represented by three main species of thegenus Apis, viz. A. dorsata Fab., A. mellifera L., and A. cerana indica Fab. Among the non apis bees of family Melliponae: Melliponinae (Tetragonula laeviceps) and Xylocopidae: Xylocopinae (Xylocopa aestuans L.) were observed to constituted 9.10 per cent and 2.07 per cent respectively. In addition to this some Hemipterans, Lepidopterans and Coleopterans were also found on mango inflorescence that contributed 0.17, 0.20 and 0.42 per cent, respectively.